Interpreting Islamic Doctrine as The Religion of Liberation in Education (Considering The Thoughts of Asghar Ali Engineer) - Karwadi Karwadi; Aninditya Sri Nugraheni; Shindy Lestari (Universitas Teuku Umar, 2021)
Education must be returned to its original khittah, that is, to humanize man with all the potential he has. In this framework, important efforts in the of Islamic liberation must be the spirit and foundation of ontological, epistemological as well as axiological education. Among the contemporary Islamic thoughts that give awareness that Islam has the power of liberation is the Asghar Ali Engineer which is derived primarily from the Qur'an and Sunnah. This finding can interpret the doctrine of Islam as a religion of liberation in education that weighs from the thoughts of Asghar Ali Engineer who has relevance and urgency. The results of this study explain about alternative solutions to the problems Islamic education in the era of globalization, namely: 1) greater attention to the reality of living in the world, can be used as a foundation for compiling the Islamic education curriculum. 2) Fight against the pro status quo. Islamic education should be based on the spirit of respecting humans as beings thinking, conscious, potentially and equipped with the right to determine their own life choices. 3) Side with marginalized communities and encourage them to actively participate. 4) Liberation theology emphasizes on the problem of praxis rather than on abstract-speculative thoughts. So that the nuances of Islamic education are quite felt is the pressure on the rational, intellectual, ethical aspects, very few that enter the applied area, skills or technology as one of the meanings that can be taken from the spirit of Islamic liberation theology.